Comparison of the Electrochemical Performance and Thermal Stability for Three Kinds of Charged Cathodes - Zhong, Guobin; Gong, Jinqiu; Wang, Chao; Xu, Kaiqi; Chen, Haodong (Frontiers in Energy Research, 2018)
The electrochemical performance and thermal stability of Li(Ni0.5Co0.2Mn0.3)O2, LiMn2O4 and LiFePO4 are investigated by the multi-channel battery cycler, electrochemical workstation, thermogravimetric analysis (TGA) and C80 instrument in this work. For electrochemical performance, Li(Ni0.5Co0.2Mn0.3)O2 shows the highest specific capacity but the worst cycle stability. For the thermal stability, the experimental results of thermogravimetry and C80 indicate that the charged Li(Ni0.5Co0.2Mn0.3)O2 has the worst thermal stability compared with charged LiFePO4 and LiMn2O4. It is also testified by calculating the chemical kinetic parameters of cathode materials based on the Arrhenius law. The pure Li(Ni0.5Co0.2Mn0.3)O2 starts to self-decompose at around 250 °C with total heat generation of -88 J/g. As for a full battery, the total heat generation is -810 J/g with exothermic peak temperature of 242 °C. The present results show that thermal runaway is more likely to occur for. Li(Ni0.5Co0.2Mn0.3)O2 with the full battery.